2018
DOI: 10.1111/bph.14480
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine residues in mitochondrial intermembrane space proteins: more than just import

Abstract: The intermembrane space (IMS) is a very small mitochondrial sub-compartment with critical relevance for many cellular processes. IMS proteins fulfil important functions in transport of proteins, lipids, metabolites and metal ions, in signalling, in metabolism and in defining the mitochondrial ultrastructure. Our understanding of the IMS proteome has become increasingly refined although we still lack information on the identity and function of many of its proteins. One characteristic of many IMS proteins are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 149 publications
(203 reference statements)
0
42
0
Order By: Relevance
“…Proteins of the mitochondrial intermembrane space (IMS) fulfill numerous critical functions, including enzymatic functions in metabolic pathways such as pyrimidine, lipid and heme biosynthesis, functions in the maintenance of mitochondrial morphology and dynamics, in assembly of the respiratory chain, and in maintenance of the mitochondrial proteome [ 1 5 ]. All IMS proteins are nuclear encoded and synthesized at cytosolic ribosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of the mitochondrial intermembrane space (IMS) fulfill numerous critical functions, including enzymatic functions in metabolic pathways such as pyrimidine, lipid and heme biosynthesis, functions in the maintenance of mitochondrial morphology and dynamics, in assembly of the respiratory chain, and in maintenance of the mitochondrial proteome [ 1 5 ]. All IMS proteins are nuclear encoded and synthesized at cytosolic ribosomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that many proteins in the intermembrane space (IMS) contain conserved cysteine-rich sections [40]. There is still no explanation for the function of these tracts [40]. It should be noted that according to our previous results, the second most susceptible AA is cysteine [10].…”
Section: Discussionmentioning
confidence: 59%
“…For example, the proteins of the respiratory chain are embedded in membranes while one side is in contact with a more aggressive environment [39]. It is well known that many proteins in the intermembrane space (IMS) contain conserved cysteine-rich sections [40]. There is still no explanation for the function of these tracts [40].…”
Section: Discussionmentioning
confidence: 99%
“…Classical substrates of this pathway are small proteins that share characteristic folds and cysteine patterns. Recently, several non‐conventional substrates were identified that do not fit these features demonstrating that the disulfide relay possesses a high degree of substrate versatility (Habich et al , ).…”
Section: The Proteasome Controls Disulfide Relay‐mediated Protein Impmentioning
confidence: 99%